Clarence Darrow papers - Darrow, Clarence, 1857-1938.; Stone, Irving, 1903-1989.
Correspondence, writings, legal records, and other papers. The bulk of the papers are correspondence, notes and printed matter collected by Irving Stone while writing a biography of Darrow and relate primarily to Darrow's literary activities and to his Chicago law practice. Subjects include capital punishment, evolution, John Thomas Scopes evolution trial, Joseph Conrad, labor, prohibition, religion, and the U.S. Anthracite Coal Strike Commission (1902). Correspondents include Ruby Darrow, Lillian Gish, Bolton Hall, Frank Harris, John Haynes Holmes, Nathan Freudenthal Leopold, Richard A. Loeb, James B. McNamara, W. Somerset Maugham, Donald R. Richberg, Charles Edward Russell, Walter Francis White, and Brand Whitlock.
Author, lecturer, lawyer, and reformer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Darrow, Ruby, -- 1869-1957 -- Correspondence; Conrad, Joseph, -- 1857-1924.; Gish, Lillian, -- 1893-1993 -- Correspondence; Hall, Bolton, -- 1854-1938 -- Correspondence; Harris, Frank, -- 1856-1931 -- Correspondence; Holmes, John Haynes, -- 1879-1964 -- Correspondence; Leopold, Nathan Freudenthal, -- 1904-1971 -- Correspondence; Loeb, Richard A., -- 1905-1936 -- Correspondence; McNamara, James B. -- 1882-1941 -- Correspondence; Maugham, W. Somerset -- 1874-1965 -- Correspondence; Richberg, Donald R. -- 1881-1960 -- Correspondence; Russell, Charles Edward, -- 1860-1941 -- Correspondence; Scopes, John Thomas -- Trials, litigation, etc; White, Walter Francis, -- 1893-1955 -- Correspondence; Whitlock, Brand, -- 1869-1934 -- Correspondence; United States. -- Anthracite Coal Strike Commission; American literature; Anthracite Coal Strike, Pa., 1902.; Capital punishment; Evolution (Biology); Labor laws and legislation; Practice of law -- Illinois -- Chicago; Prohibition; Religion; Social problems; Strikes and lockouts -- Coal mining -- Pennsylvania; Authors; Lecturers; Lawyers; Reformers